Pulse wave velocity 24-hour monitoring with one-site measurements by oscillometry - Posokhov IN (Medical Devices : Evidence and Research, 2013)
Igor N PosokhovHemodynamic Laboratory Ltd, Nizhniy Novgorod, RussiaAbstract: This review describes issues for the estimation of pulse wave velocity (PWV) under ambulatory conditions using oscillometric systems. The difference between the principles of measuring the PWV by the standard method and by oscillometry is shown, and information on device validation studies is summarized. It was concluded that currently oscillometry is a method that is very convenient to use in the 24-hour monitoring of the PWV, is relatively accurate, and is reasonably comfortable for the patient. Several indices with the same principles as those in the analysis of blood pressure in ambulatory monitoring of blood pressure, namely the assessment of load, variability, and circadian rhythm, are proposed.Keywords: pulse wave velocity, 24-hour monitoring, oscillometry